The Effect of Continuous Running Training Programs and Interval Training Programs in Improving Physical Fitness - Asma Bara; Tatang Muhtar; Dewi Susilawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study carried out an in-depth analysis of two popular physical training programs: continuous running and interval training. The research method involved a number of statistical tests, including checking the normality of data distribution, uniformity analysis, and independent T tests. Participants from both training programs were used to gain a more detailed understanding of the nature of each program and comparisons of performance between the two. The analysis results show that continuous running approaches a normal data distribution, indicating data stability and consistency. Meanwhile, the finding that performance variability was similar across the two programs led to new insights into the consistency of performance within the groups. The main finding was the superiority of continuous running in performance gains, with average scores consistently higher than interval training. This indicates the potential of continuous running in increasing physical capacity and endurance. The practical implications are relevant for the design of exercise programs, providing guidance for coaches and individuals seeking improved physical performance. Although the results show the superiority of continuous running, interval training may require adapting strategies to achieve better results. This research also opens up opportunities for further research, especially in understanding the factors that influence achievement in these two training programs. Further exploration of variations in training duration, intensity and frequency in the context of both could provide new insights into the world of fitness and sport. These findings provide a strong empirical basis for decisions regarding physical exercise programs, support data-driven decision making, and provide insight into scientific approaches in guiding more effective and efficient physical exercise practices.